A new shape memory alloy film/p-Si solar light four quadrant detector for solar tracking applications - Canbay, C. Aksu; Tataroglu, A.; Dere, A.; Al-Ghamdi, Ahmed; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2016)
Shape memory alloys (SMAs) are promising materials for industrial and electronic actuators applications. The Cu-Al-Mn-Ni shape memory alloy was coated as a Schottky contact on p-Si substrate to fabricate a four quadrant sensor using a vacuum coating system. A front illuminated shape memory film-p-type silicon -based four-quadrant solar light Schottky sensor was fabricated using the various metal contact masks. The electrical and photoresponse properties of Cu-Al-Mn-Ni/p-Si diode were investigated. These properties of the diode were analyzed under in a wide range of frequencies and illumination intensities. The reverse current of the diode increases with increasing illumination intensities. This result confirms that the diode exhibits both photoconducting and photovoltaic behavior. The forward bias current of the diode increases exponentially with voltage confirming rectification behavior. Electronic parameters such as ideality factor, barrier height and series resistance of the diode were determined from I-V characteristics and Cheung's functions. The transient photocurrent, photocapacitance and photoconductance measurements indicate that the diode is very sensitive to illumination. Also, the admittance measurements of the diode exhibited a decrease in capacitance and increase in conductance with increasing frequency. The frequency dependence of capacitance and conductance is attributed to the presence of interface states. It is evaluated that Cu-Al-Mn-Ni/p-Si shape memory alloy film/p-Si based four quadrant detector can be used in solar tracking applications. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Shape memory alloy; Cu-Al-Mn-Ni; I/C/G-V characteristics; Transient measurements